Assessment of Selected Aspects of Teaching Programming in SK and CZ - Ján ZÁHOREC (Informatics in Education, 2014)
Authors of this paper carried out a broader international research aimed at assessing the computer science education at upper secondary level of education - ISCED 3A. The assessed school subjects were informatics and programming as the most common school subjects taught at secondary schools within computer sciences. The assessment was based on the students' evaluations, their points of view and opinions, what was a specific feature of the research. The paper presents main findings and results for the school subject programming obtained in Slovakia (SK) and the Czech Republic (CZ). As a weakness of teaching programming in both countries inadequate quality of textbooks or a lack of appropriate textbooks in general was identified. As strength of the programming teaching in the Czech Republic attractiveness of the content of the school subject programming (its curriculum) was identified and in Slovakia it was the clearness of teachers' presentations of teaching material.